Analisis Pentingnya Berpikir Kritis pada Operasi Membulatkan Angka Kelas IV Pembelajaran Matematika (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The problem of this study is the lack of students' critical thinking skills in mathematics learning. The purpose of this text is to describe critical thinking in mathematics. The methodology used in the research of this article is qualitative. One of the methods used is qualitative using data collection techniques in the form of diagnostic tests. From several sources obtained, the most relevant data related to this article are presented. The ability to think critically has been proven to have a very important role in learning the material rounding numbers. Students who have good critical thinking skills are not only able to apply rounding rules mechanically, but also understand basic concepts and can apply them in various problem contexts. This study recommends the importance of integrating learning strategies that can develop students' critical thinking skills in mathematics learning, especially through problem-based learning approaches and contextual learning.